Indonesian Interference toward English Used on Outdoor Advertisement Boards and Banner in Sukoharjo, Central Java - Giyatmi, Giyatmi -; Astuti, Purwani Indri; Wijayava, Ratih -; Arumi, Sihindun - (Lingual Journal of Language and Culture, 2019)
Interference is a common phenomenon in second language learning. However, the researchers are interested in analyzing interference from another point of view. This research aims at finding the types of Indonesian interference toward English found in outdoor advertisement boards and banners in Sukoharjo. The researchers use some theories dealing with interference such as the definition of interference and type of interference. This research belongs to a descriptive qualitative research. Data of this research are English words, phrases, and sentences consisting of Indonesian interference toward English used in outdoor advertisement boards and banner. The data are taken from outdoor advertisement boards and banners in Sukoharjo. The technique of data collection used is observation then followed by writing technique. English words, phrases, and sentences with no interference are reduced. Then the data found are encoded with No data/Data/Kinds of Interference. The researchers use theory triangulation during this research. The researchers found 74 data of Indonesian interference toward English in outdoor advertisement boards and banners in Sukoharjo. After analyzing the data, the researchers found that there are 6 types of Indonesian interference toward English; (1) syntactic interference in the formation of phrase and sentence (2) Lexical interference in the case of borrowing words adapted into Indonesian spelling (3) Phonological interference in vowel sounds, consonant sounds, and semivowel sounds (4) Morphological interference in the process of affixation (5) Graphic interference in the spelling principle (6) Translation interference which happens because of direct translation. Keywords: advertisement, language interference, kinds of interferences.